Max Helsing and the thirteenth curse - Jobling, Curtis (Max Helsing: Monster Hunter, 2015)
"Max van Helsing and a group of friends try to save the world after he discovers he has been cursed by an evil warlock who intends to reclaim the earth for monsters"--